Positive electrode composite material and electrolyte of aqueous zinc ion battery and application of positive electrode composite material and electrolyte

The ZnV8O20·nH2O@Zn3(OH)2V2O7·2H2O composite material prepared by ion pre-insertion and heterostructure design combined with Zn(CF3SO3)2 and ZnSO4 mixed electrolyte, solved the problem of dissolution of the positive electrode material of the aqueous zinc ion battery and the growth of the zinc negative dendrites, significantly improving the cycle stability and safety of the battery.

CN119774657AActive Publication Date: 2025-04-08CHINA JILIANG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510265438.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-08
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

The problems of long-term cycle stability and battery safety of aqueous zinc ion batteries, especially the dissolution of the positive electrode material and the growth of the dendrites of the zinc negative electrode, affect the cycle life and safety of the battery.

Method used

Using ion pre-insert method and heterostructure design, zinc citrate and vanadium pentoxide were prepared by heating reaction of autoclave to prepare ZnV8O20·nH2O@Zn3(OH)2V2O7·2H2O composite material, and Zn(CF3SO3)2 and ZnSO4 mixed electrolyte was used.

Benefits of technology

The specific capacity and cycle stability of the positive electrode material are significantly improved, the cycle life of the battery is extended, and the dendrites of the negative electrode are suppressed, enhancing the overall stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774657A_ABST
    Figure CN119774657A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode composite material and electrolyte of an aqueous zinc ion battery and application of the positive electrode composite material and the electrolyte. According to the preparation method, an ion pre-insertion method and a heterostructure design are adopted, vanadium pentoxide and zinc citrate are mixed and heated to react, and the ZVO-ZVOH composite material is formed. The material has abundant heterogeneous boundaries and active sites, and can be used as a positive electrode material of a zinc ion battery, so that the problem of chemical dissolution in the cyclic process of a vanadium-based compound is remarkably solved. A heterogeneous boundary in ZVO and ZVOH is beneficial to electron transmission and provides more Zn < 2 + > storage sites, so that the rate capability is effectively improved; the ZVOH effectively inhibits the dissolution problem of the positive electrode in the circulation process, so that the circulation stability is effectively improved. And the mixed Zn (CF3SO3) 2 and ZnSO4 electrolyte can be used for effectively reducing the dissolution of ZVO and ZVOH and inhibiting the dendritic crystal growth of the Zn negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aqueous zinc ion batteries, and in particular to a positive electrode composite material and an electrolyte of an aqueous zinc ion battery and applications thereof. Background Art

[0002] Aqueous zinc-ion batteries (AZIBs) have attracted widespread attention due to their unique advantages. Compared with lithium, zinc resources are more abundant and the cost is lower, and aqueous electrolytes have the advantages of being non-flammable, non-explosive, non-toxic and non-polluting. At the same time, the multivalent ions in the aqueous electrolyte provide a higher theoretical capacity and energy density, further improving the performance of AZIBs. However, problems with AZIBs in long-term cycle stability and battery safety still exist and need to be solved urgently.

[0003] The performance of AZIBs is mainly determined by the selection of positive electrode materials and the stability of negative electrode materials. At present, common positive electrode materials include manganese oxides, vanadium-based compounds, and Prussian blue analogs. Manganese oxides have a high theoretical capacity, but their cycle stability is poor due to irreversible phase changes during the charge and discharge process; Prussian blue analogs usually have a low specific capacity and poor cycle performance. Therefore, vanadium-based compounds, especially vanadium oxides, can achieve more electron transfer in redox reactions due to their rich layered structure and multivalent state characteristics, and exhibit higher capacity. However, during the electrochemical reaction, the interaction between free water (H2O) and vanadium (V) atoms causes the dissolution of the positive electrode material, which seriously affects the cycle life and safety of the battery.

[0004] To overcome this problem, researchers have proposed a variety of innovative strategies, such as suppressing the dissolution of vanadium by modifying the surface of the material or introducing a new interface layer. x (OTf) y (OH) 2x-y nH2O introduces V6O 13 In the process of electrochemical reaction, the Zn3V2O7(OH)2·2H2O layer was prepared in situ on the surface of V2O5 electrode by atomic layer deposition technology, which can effectively improve the stability of vanadium-based positive electrode and promote the Zn 2+ Although these methods have improved the stability of the positive electrode to a certain extent, how to further improve the cycle life while maintaining a high capacity remains a technical problem that needs to be solved.

[0005] In addition, the stability of the zinc negative electrode in AZIBs also faces severe challenges. In order to inhibit the growth of zinc dendrites, researchers have tried to improve the stability of the zinc negative electrode through electrolyte modification and negative electrode protective layer strategies. Although in some electrolytes, such as Zn(CF3SO3)2, the dissolution of the vanadium-based positive electrode can be effectively inhibited and the negative electrode can be stabilized, a single electrolyte cannot maintain the stability of the positive and negative electrodes at the same time. Therefore, how to balance the interaction between the positive and negative electrodes while ensuring the stability of the positive and negative electrodes to build a highly stable and long cycle life aqueous zinc-ion battery is still the difficulty and key to current research. Summary of the invention

[0006] In view of this, the present invention provides a positive electrode composite material and an electrolyte for an aqueous zinc ion battery and applications thereof, the main purpose of which is to provide a positive electrode composite material that can effectively increase the capacity of the positive electrode while enhancing ion mobility and battery stability.

[0007] In order to achieve the above object, the present invention mainly provides the following technical solutions: In one aspect, the present invention provides a positive electrode composite material for an aqueous zinc ion battery, wherein the positive electrode composite material is prepared from zinc citrate and vanadium pentoxide by the following steps: 1) Weigh zinc citrate and vanadium pentoxide in a mass ratio of (0.03-0.8):1; add vanadium pentoxide into deionized water and 30wt% hydrogen peroxide as solvent and stir for 1 to 3 h to prepare a vanadium pentoxide solution; 2) Add zinc citrate to the vanadium pentoxide solution and stir for 25 to 35 minutes to form an orange-red mixture; 3) The orange-red mixture is placed in an autoclave for heating and reaction to obtain the positive electrode composite material.

[0008] In the present invention, the positive electrode composite material is also referred to as ZnO 20 ·nH2O(ZVO)@Zn3(OH)2V2O7·2H2O(ZVOH) composite material.

[0009] Preferably, in step 1), the volume ratio of deionized water to 30 wt% hydrogen peroxide is 40:1.

[0010] Preferably, the concentration of the vanadium pentoxide solution prepared in step 1) is 0.025 mol / L.

[0011] Preferably, the mass ratio of the zinc citrate and vanadium pentoxide prepared in step 1) is preferably 0.165:1.

[0012] Preferably, in step 3), the heating time of the autoclave is 10 h to 14 h, and the heating temperature ranges from 110° C. to 130° C.

[0013] Preferably, the step 3) further comprises the following steps: repeatedly washing the positive electrode composite material with deionized water, and obtaining a powder material after drying.

[0014] Preferably, the drying temperature of the drying treatment is 60° C. to 80° C., and the drying time is 12 h to 16 h.

[0015] On the other hand, the present invention also provides a mixed electrolyte for an aqueous zinc ion battery, which is used in combination with the above-mentioned positive electrode composite material, and the mixed electrolyte is a mixture of 2 mol / L Zn(CF3SO3)2 and 1 mol / L ZnSO4 electrolyte.

[0016] Preferably, the concentration of the Zn(CF3SO3)2 electrolyte is 2 mol / L, and the concentration of the ZnSO4 electrolyte is 1 mol / L; the molar ratio of Zn(CF3SO3)2 and ZnSO4 in the mixed electrolyte is (0.1-2): (0.01-1).

[0017] Another aspect of the present invention provides an aqueous zinc ion battery, wherein the positive electrode material comprises any of the above positive electrode composite materials; and the electrolyte is any of the above mixed electrolytes. Specifically, the positive electrode composite material is applied to the positive electrode material of the zinc ion battery, and is arranged at the positive electrode of the zinc ion battery, and the molar ratio of Zn(CF3SO3)2 and ZnSO4 is (0.1-2): (0.01-1) as the electrolyte, and Zn foil is the negative electrode, and the battery is assembled into a full battery.

[0018] Compared with the prior art, the present invention prepares ZVO@ZVOH composite material by ion pre-insertion method, which has the following significant technical effects: 1. The “zinc-rich” ZVO@ZVOH with a dual-phase vanadate structure was prepared by a one-step hydrothermal method.

[0019] 2. The rich heterogeneous boundaries in the structure facilitate electron transport and provide more Zn 2+ storage sites, reducing diffusion resistance in the electrode.

[0020] 3. ZVOH effectively maintains the stability of the positive electrode during the cycle, and the composite material exhibits high specific capacity and long cycle life.

[0021] 4. The mixed Zn(CF3SO3)2 and ZnSO4 electrolyte can effectively reduce the dissolution of ZVO@ZVOH and inhibit the dendrite growth of Zn anode.

[0022] 5. This material does not require calcination during the preparation process, and is energy-saving and environmentally friendly.

[0023] Therefore, the present invention provides an efficient and sustainable method for preparing a positive electrode material and a mixed electrolyte, which significantly enhances the electrical performance of a zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The X-ray diffraction spectrum of the ZVO@ZVOH-S2 composite material provided in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the ZVO@ZVOH-S2 composite material provided in Example 1 of the present invention; Figure 3 A high magnification transmission electron microscope image of the ZVO@ZVOH-S2 composite material provided in Example 1 of the present invention; Figure 4 The cyclic voltammetry curve of the ZVO@ZVOH-S2 composite material provided in Example 1 of the present invention as a positive electrode material for a zinc ion battery; Figure 5 A cycle performance diagram of a zinc ion battery prepared in Example 1 provided by the present invention; Figure 6 A cycle performance diagram of a zinc ion battery prepared in Comparative Example 1 provided by the present invention; Figure 7 A cycle performance diagram of a zinc ion battery prepared in Comparative Example 2 provided by the present invention; Figure 8 A cycle performance diagram of a zinc ion battery prepared in Comparative Example 3 provided by the present invention; Fig. 9 This is a cycle performance diagram of a zinc ion battery prepared in Comparative Example 4 provided by the present invention. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0026] In one aspect, an embodiment of the present invention provides a composite material, comprising: Zinc citrate and vanadium pentoxide, wherein the mass ratio of the zinc citrate to the vanadium pentoxide is (0.03-0.8):1.

[0027] In the ZVO@ZVOH composite material of the present invention, the heterogeneous boundary in ZVO@ZVOH facilitates electron transport and provides more Zn 2+Storage sites, thereby effectively improving rate performance; ZVOH effectively inhibits the dissolution of the positive electrode during the cycle, thereby effectively increasing the cycle stability. The mixed electrolyte of Zn(CF3SO3)2 and ZnSO4 can effectively reduce the dissolution of ZVO@ZVOH and inhibit the dendrite growth of the Zn negative electrode.

[0028] On the other hand, an embodiment of the present invention further provides a method for preparing a composite material, comprising the following steps: (1) Weigh zinc citrate and vanadium pentoxide according to mass ratio to prepare a vanadium pentoxide solution; (2) adding zinc citrate to the vanadium pentoxide solution and stirring to form an orange-red mixture; (3) The orange-red mixture was placed in an autoclave and heated to react to obtain the ZVO@ZVOH composite material.

[0029] Finally, the present invention also provides a method for mixing electrolytes, wherein the molar ratio of Zn(CF3SO3)2 and ZnSO4 electrolytes is (0.1-2): (0.01-1). The above positive electrode composite material and the mixed electrolyte are assembled into a full battery.

[0030] The present invention adopts an ion pre-insertion method and a heterogeneous design to mix vanadium pentoxide and zinc citrate and heat the mixture to form a ZVO@ZVOH composite material. The ZVO@ZVOH material with abundant boundaries and active sites is used as the positive electrode material of the zinc ion battery. The heterogeneous boundaries in ZVO@ZVOH facilitate electron transport and provide more Zn 2+ Storage sites, thereby effectively improving rate performance; ZVOH effectively inhibits the dissolution of the positive electrode during the cycle, thereby effectively increasing the cycle stability. The mixed electrolyte of Zn(CF3SO3)2 and ZnSO4 can effectively reduce the dissolution of ZVO@ZVOH and inhibit the dendrite growth of the Zn negative electrode.

[0031] Example 1 An embodiment of the present invention provides a method for preparing a composite material, comprising the following steps: 100. Weigh zinc citrate and vanadium pentoxide in a mass ratio of 0.165:1.

[0032] 101. Add 0.182 g of vanadium pentoxide to 40 mL of a solution containing deionized water and 30 wt% hydrogen peroxide in a volume ratio of 40:1.

[0033] 102. Stir for 1 hour to obtain an orange-red vanadium pentoxide solution, wherein the concentration of the vanadium pentoxide solution is 0.025 mol / L.

[0034] 103. Add zinc citrate to the vanadium pentoxide solution and stir for 25 minutes to form an orange-red mixture.

[0035] 104. The orange-red mixture is placed in an autoclave for heating reaction. The heating time is 6 hours and the heating temperature is 120°C to obtain a ZVO@ZVOH composite material.

[0036] 105. The composite material is repeatedly rinsed with deionized water, and then dried at a temperature of 60° C. for 12 h to obtain a powder material.

[0037] 106. Mix 2 mol / L Zn(CF3SO3)2 and 1 mol / L ZnSO4 electrolyte in a molar ratio of 2:1, and stir to obtain a mixed electrolyte.

[0038] like Figure 1 As shown, the composite material is represented by the code ZVO@ZVOH-S2, and the diffraction peaks at 8.3° and 25.62° correspond to CaV8O 20 The characteristic peaks of ·xH2O (PDF#45-1362). The diffraction peaks at 12.3° and 30.16° correspond to the characteristic peaks of Zn3(OH)2V2O7·2H2O (PDF#50-0570).

[0039] like Figure 2 As shown, the ZVO@ZVOH sample exhibits a microsphere aggregation morphology, in which the smallest microsphere has a diameter of about 0.2 μm and the largest microsphere is 8.0 μm.

[0040] like Figure 3 As shown in the figure, it can be seen that the ZVO@ZVOH material is composed of uniform nanorods. In the high-resolution TEM, the heterogeneous interface and lattice fringes can be observed. 0.194nm and 0.125nm are the lattice fringes of the (60-1) and (005) crystal planes corresponding to ZVO, respectively, and 0.201nm is the (120) lattice fringes corresponding to ZVOH.

[0041] The present invention uses CR2032 coin cells to test the electrochemical performance of the composite ZVO@ZVOH-S2 material. When preparing the electrode, 70% ZVO@ZVOH-S2 active material, 20% Super P and 10% polyvinylidene fluoride (PVDF) are mixed and dispersed using N-methylpyrrolidone (NMP) to form a uniform slurry. Then, the slurry is coated on a titanium foil and dried under a vacuum environment at 60 °C for 12 h. The mass loading is about 1.8 mg cm -2Electrode. When assembling zinc ion batteries, glass fiber is used as a separator, Zn(CF3SO3)2 and ZnSO4 are used as electrolytes, and zinc foil is used as a counter electrode. All components are assembled into CR2032 type ZIBs in air. Cyclic voltammetry (CV) performance tests are performed using an electrochemical workstation with a scanning voltage range of 0.3-1.5 V. In the CV curve, two pairs of redox peaks can be clearly observed, located at 1.02 V / 0.96 V and 0.62 V / 0.59 V, respectively, and two reduction peaks at 0.45 V and 0.82 V, corresponding to V 5+ / V 4+ and V 4+ / V 3+ The transformation, such as Figure 4 As shown. At 0.3 A g -1 At this current density, the specific capacity of the battery reaches 340.2 mA h g after 2 cycles. -1 After 200 cycles, the specific capacity remained at 304.7 mA h g -1 , the capacity retention rate is about 89.6%. Figure 5 These data indicate that the battery has excellent cycling stability and electrochemical performance.

[0042] In this embodiment, ion pre-insertion method and heterogeneous structure design are adopted to mix vanadium pentoxide and zinc citrate and heat the mixture to form ZVO@ZVOH composite material. ZVO@ZVOH material with abundant boundaries and active sites is used as the positive electrode material of zinc ion battery. The heterogeneous boundaries in ZVO@ZVOH are conducive to electron transport and provide more Zn 2+ Storage sites, thereby effectively improving rate performance; ZVOH effectively inhibits the dissolution of the positive electrode during the cycle, thereby effectively increasing the cycle stability. The mixed electrolyte of Zn(CF3SO3)2 and ZnSO4 can effectively reduce the dissolution of ZVO@ZVOH and inhibit the dendrite growth of the Zn negative electrode.

[0043] Example 2 The present invention provides a method for preparing a second composite material, comprising the following steps: 200. Weigh zinc citrate and vanadium pentoxide in a mass ratio of 0.03:1.

[0044] 201. Add 0.182 g of vanadium pentoxide to 40 mL of a solution containing deionized water and 30 wt% hydrogen peroxide in a volume ratio of 40:1.

[0045] 202. Stir for 2 h to obtain an orange-red vanadium pentoxide solution, wherein the concentration of the vanadium pentoxide solution is 0.025 mol / L.

[0046] 203. Add zinc citrate to the vanadium pentoxide solution and stir for 30 minutes to form an orange-red mixture.

[0047] The orange-red mixture was placed in an autoclave for heating reaction. The heating time was 7 h and the heating temperature was 100° C. to obtain a ZVO@ZVOH composite material.

[0048] The composite material is repeatedly rinsed with deionized water, and then dried at a temperature of 70° C. for 14 h to obtain a powder material.

[0049] 206. Mix 2 mol / L Zn(CF3SO3)2 and 1 mol / L ZnSO4 electrolyte in a molar ratio of 2:1, and stir to obtain a mixed electrolyte.

[0050] A mixture of vanadium pentoxide and zinc citrate is chemically reacted in a high temperature and high pressure environment to obtain a ZVO@ZVOH composite material, denoted by the code ZVO@ZVOH-S1.

[0051] The diffraction peaks of ZVO@ZVOH-S1 are very similar to those of ZVO@ZVOH-S2, but the diffraction peaks of ZVO@ZVOH-S1 are weaker than those of ZVO@ZVOH-S2. Referring to the method of Example 1, ZVO@ZVOH-S1 was used as the positive electrode material, Zn(CF3SO3)2 and ZnSO4 were used as the electrolyte, and zinc foil was used as the counter electrode to assemble a zinc ion battery. The battery was heated to 0.3 A g -1 After running for 10 cycles at the current density, the specific capacity reached 267.4 mA h g -1 ; After running 200 cycles, the capacity retention rate relative to the 10th cycle is about 81.2%.

[0052] Example 3 The present invention provides a third method for preparing a composite material, comprising the following steps: 300. Weigh zinc citrate and vanadium pentoxide in a mass ratio of 0.8:1.

[0053] 301. Add 0.182 g of vanadium pentoxide to 40 mL of a solution containing deionized water and 30 wt% hydrogen peroxide in a volume ratio of 40:1.

[0054] 302. Stir for 3 hours to obtain an orange-red vanadium pentoxide solution, wherein the concentration of the vanadium pentoxide solution is 0.025 mol / L.

[0055] 303. Add zinc citrate to the vanadium pentoxide solution and stir for 35 minutes to form an orange-red mixture.

[0056] 304. The orange-red mixture is placed in an autoclave for heating reaction. The heating time is 6 hours and the heating temperature is 130° C. to obtain a ZVO@ZVOH composite material.

[0057] 305. The composite material is repeatedly rinsed with deionized water, and then dried at a temperature of 70° C. for 14 hours to obtain a powder material.

[0058] 306. Mix 2 mol / L Zn(CF3SO3)2 and 1 mol / L ZnSO4 electrolyte in a molar ratio of 2:1, and stir to obtain a mixed electrolyte.

[0059] A mixture of vanadium pentoxide and zinc citrate is chemically reacted in a high temperature and high pressure environment to obtain a ZVO@ZVOH composite material, denoted by the code ZVO@ZVOH-S3.

[0060] Referring to the method of Example 1, ZVO@ZVOH-S3 was used as the positive electrode material, Zn(CF3SO3)2 and ZnSO4 were used as the electrolyte, and zinc foil was used as the counter electrode to assemble a zinc ion battery. The battery was -1 After running for 10 cycles at the current density, the specific capacity reached 246.2 mA h g -1 ; After running 200 cycles, the capacity retention rate relative to the first cycle is about 75.7%.

[0061] Example 4 The present invention provides a fourth method for preparing a composite material, comprising the following steps: 400. Weigh zinc citrate and vanadium pentoxide in a mass ratio of 0.6:1.

[0062] 401. Add 0.182 g of vanadium pentoxide to 40 mL of a solution containing deionized water and 30 wt% hydrogen peroxide in a volume ratio of 40:1.

[0063] 402. Stir for 3 hours to obtain an orange-red vanadium pentoxide solution, wherein the concentration of the vanadium pentoxide solution is 0.025 mol / L.

[0064] 403. Add zinc citrate to the vanadium pentoxide solution and stir for 35 minutes to form an orange-red mixture.

[0065] 404. The orange-red mixture is placed in an autoclave for heating reaction. The heating time is 10 h and the heating temperature is 110° C. to obtain a ZVO@ZVOH composite material.

[0066] 405. The composite material is repeatedly rinsed with deionized water, and then dried at a temperature of 80° C. for 16 hours to obtain a powder material.

[0067] 406. Mix 2 mol / L Zn(CF3SO3)2 and 1 mol / L ZnSO4 electrolyte in a molar ratio of 2:1, and stir to obtain a mixed electrolyte.

[0068] A mixture of vanadium pentoxide and zinc citrate is chemically reacted in a high temperature and high pressure environment to obtain a ZVO@ZVOH composite material, which is denoted by the code ZVO@ZVOH-S4.

[0069] Referring to the method of Example 1, ZVO@ZVOH-S4 was used as the positive electrode material, Zn(CF3SO3)2 and ZnSO4 were used as the electrolyte, and zinc foil was used as the counter electrode to assemble a zinc ion battery. The battery was -1 After running for 10 cycles at the current density, the specific capacity reached 215.2 mA h g -1 ; After running 200 cycles, the capacity retention rate relative to the first cycle is about 65%.

[0070] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the mass ratio of zinc citrate to vanadium pentoxide is 0.01:1, and the obtained composite material is denoted by code ZVO.

[0071] Referring to the method of Example 1, ZVO was used as the positive electrode material, and a detailed X-ray diffraction (XRD) test and zinc ion battery performance evaluation were performed. The diffraction peaks of ZVO at 8.3° and 25.62° correspond to ZnV8O 20 The characteristic peaks of xH2O (PDF#45-1362) correspond to the (001) and (110) crystal planes respectively; in addition, there are no other impurity peaks in the XRD spectrum, which confirms that ZVO is composed of a single phase. Figure 6 As shown in the figure, as the positive electrode material, 2M Zn(CF3SO3)2 and 1M ZnSO4 were used as the electrolyte, and zinc foil was used as the counter electrode to assemble the zinc ion battery. -1 After running for 2 cycles at the current density, the specific capacity reached 291 mA h g -1 ; After running 100 cycles, the specific capacity reaches 210 mA hg -1 The relative capacity retention rate of the second cycle is about 71.8%. In Example 1, after the battery runs for 2 cycles under the same conditions, the specific capacity reaches 340.2 mA hg - ¹, after 200 cycles, the specific capacity remains at 304.7 mA h g -1The capacity retention rate of the second cycle is about 89.6%. The specific capacity and capacity retention rate of Comparative Example 1 are significantly lower than those of Example 1.

[0072] This significant difference shows that the electrochemical performance of ZVO@ZVOH material is better than that of ZVO material. The larger migration energy and easier solubility of ZVO lead to a significant decrease in its specific capacity and capacity retention rate. Therefore, by introducing ion pre-embedding and heterogeneous structure into vanadium-based compounds, the electrochemical performance of the positive electrode material can be effectively improved, the specific capacity can be increased, and the cycle life can be improved. This comparison result demonstrates the superiority of the ZVO@ZVOH composite material of the present invention in the application of zinc-ion batteries.

[0073] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the mass ratio of zinc citrate to vanadium pentoxide is 1:1, and the obtained composite material is denoted by code ZVOH.

[0074] Referring to the method of Example 1, ZVOH was used as the positive electrode material, 2 mol / L Zn(CF3SO3)2 and 1 mol / L ZnSO4 were used as the electrolyte, and zinc foil was used as the counter electrode to assemble a zinc ion battery. Figure 7 As shown, the battery is at 0.3 A g -1 After running for 2 cycles at the current density, the specific capacity reached 174 mA h g -1 After running for 100 cycles, its specific capacity dropped significantly to 124 mA h g -1 , the capacity retention rate relative to the first cycle is about 71.3%. The specific capacity and capacity retention rate of comparative example 2 are much lower than those of example 1.

[0075] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the molar ratio of Zn(CF3SO3)2 and ZnSO4 as the electrolyte is changed to 2:0.01.

[0076] Referring to the method of Example 1, ZVO@ZVOH was used as the positive electrode material, Zn(CF3SO3)2 and ZnSO4 were used as the electrolyte in a molar ratio of 2:0.01, and a zinc ion battery was assembled with zinc foil as the counter electrode. Figure 8 As shown, the battery is at 0.3 A g -1 After running for 2 cycles at the current density, the specific capacity reached 301 mA h g -1 After running for 100 cycles, its specific capacity dropped significantly to 232 mAh g -1 , the capacity retention rate relative to the first cycle is about 76.5%. The specific capacity and capacity retention rate of comparative example 3 are lower than those of example 1.

[0077] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the molar ratio of Zn(CF3SO3)2 and ZnSO4 as the electrolyte is changed to 0.1:1.

[0078] Referring to the method of Example 1, ZVO@ZVOH was used as the positive electrode material, Zn(CF3SO3)2 and ZnSO4 were used as the electrolyte in a molar ratio of 0.1:1, and a zinc ion battery was assembled with zinc foil as the counter electrode. Fig. 9 As shown, the battery is at 0.3 A g -1 After running for 2 cycles at the current density, the specific capacity reached 277 mA h g -1 After running for 100 cycles, its specific capacity dropped significantly to 144 mAh g -1 , the capacity retention rate relative to the first cycle is about 51.9%. The specific capacity and capacity retention rate of comparative example 4 are much lower than those of example 1.

[0079] From the above examples 1 to 4 and comparative examples 1 to 4, it can be seen that in example 1, zinc citrate and vanadium pentoxide are mixed and reacted to form a ZVO@ZVOH composite material through ion pre-insertion method, heterogeneous structure design and mixed electrolyte technology, and Zn(CF3SO3)2 and ZnSO4 are mixed into an electrolyte. The composite synergistic effect significantly increases the active sites of VOH, thereby significantly increasing the capacity of the positive electrode. At 1 A g -1 After 20 cycles at the current density, the battery capacity reaches 358 mA h g -1 . In addition, ZVOH effectively enhances the structural stability of VOH and significantly improves the cycle stability. Zn(CF3SO3)2 and ZnSO4 with a molar ratio of 2:1 effectively inhibit the dissolution of ZVO@ZVOH and reduce the dendrite phenomenon of the negative electrode, and the capacity retention rate is about 89.6%. Therefore, compared with other embodiments and comparative examples, Example 1 shows higher specific capacity and superior cycle performance, verifying the significant advantages of this technical path in improving battery performance.

[0080] On the other hand, an embodiment of the present invention further provides an application of a composite material, wherein the composite material is applied to a positive electrode material of a zinc ion battery and is used to be arranged at a positive electrode of the zinc ion battery. The mixed electrolyte is used as an electrolyte to assemble into a full battery.

[0081] The ZVO@ZVOH composite material prepared by the present invention is used as a positive electrode material for a zinc ion battery, and a mixed electrolyte of Zn(CF3SO3)2 and ZnSO4 is used as an electrolyte, which can have good electrical conductivity, high specific capacity and long cycle life.

[0082] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A positive electrode composite material for an aqueous zinc ion battery, characterized in that: The positive electrode composite material is prepared from zinc citrate and vanadium pentoxide by the following steps: 1) Weigh zinc citrate and vanadium pentoxide in a mass ratio of (0.03-0.8) : 1; add vanadium pentoxide into a solvent consisting of deionized water and 30wt% hydrogen peroxide and stir for 1 to 3 h to prepare a vanadium pentoxide solution; 2) Add zinc citrate to the vanadium pentoxide solution and stir for 25 to 35 minutes to form an orange-red mixture; 3) The orange-red mixture is placed in an autoclave for heating and reaction to obtain the positive electrode composite material.

2. The positive electrode composite material for aqueous zinc ion battery according to claim 1, characterized in that: In the step 1), the volume ratio of deionized water to 30 wt% hydrogen peroxide is 40:

1.

3. The positive electrode composite material for aqueous zinc ion battery according to claim 1, characterized in that: The concentration of the vanadium pentoxide solution prepared in step 1) is 0.025 mol / L.

4. The positive electrode composite material for aqueous zinc ion battery according to claim 2, characterized in that: The mass ratio of the zinc citrate and vanadium pentoxide prepared in step 1) is preferably 0.165:

1.

5. The positive electrode composite material for aqueous zinc ion battery according to claim 1, characterized in that: In the step 3), the heating time of the autoclave is 10 h to 14 h, and the heating temperature ranges from 110° C. to 130° C.

6. The positive electrode composite material for aqueous zinc ion battery according to claim 1, characterized in that: The step 3) further comprises the following steps: repeatedly washing the positive electrode composite material with deionized water, and obtaining a powder material after drying.

7. The positive electrode composite material for aqueous zinc ion battery according to claim 6, characterized in that: The drying temperature of the drying treatment is 60° C. to 80° C., and the drying time is 12 h to 16 h.

8. A mixed electrolyte for an aqueous zinc ion battery, characterized in that: Used in conjunction with the positive electrode composite material according to any one of claims 1-7, the mixed electrolyte is a mixture of Zn(CF3SO3)2 and ZnSO4 electrolytes.

9. The mixed electrolyte of the aqueous zinc ion battery according to claim 8, characterized in that: The concentration of the Zn(CF3SO3)2 electrolyte is 2 mol / L, and the concentration of the ZnSO4 electrolyte is 1 mol / L; the molar ratio of Zn(CF3SO3)2 and ZnSO4 in the mixed electrolyte is (0.1-2): (0.01-1).

10. An aqueous zinc ion battery, characterized in that: The positive electrode material comprises the positive electrode composite material described in any one of claims 1-7; and the electrolyte is the mixed electrolyte described in any one of claims 8-9.

Citation Information

Patent Citations

  • AgBr / ZVO catalyst with visible light catalytic activity as well as preparation method and application thereof

    CN107442142A

  • ZnO / V2O5 composite material for sterilization in bright and dark fields, and preparation method of composite material

    CN107455388A

  • Preparation method and application of iron-zinc vanadate ion battery positive electrode material

    CN112062160A

  • Transition metal doped V6O13 nanobelt material as well as preparation method and application thereof

    CN113929140A

  • Mixed aqueous zinc ion battery electrolyte with stable pH value and application

    CN114865110A